Chemical metallurgy - Moore, J. J. (John Jeremy), 1944- (Butterworths, 1981)
Chemical Metallurgy provides an understanding of the fundamental chemical principles and demonstrates the application of these principles to process metallurgy and corrosion protection. The book discusses the fundamental chemical principles involved in metallurgical reactions. Since it is felt that the understanding of quantitative thermodynamics and its application to process metallurgy often prove to be a major problem area for students, example calculations and exercises are included at the end of each section in Chapter 2. The final three chapters deal with the applications of the chemical.